Empirical levofloxacin-containing versus clarithromycin-containing sequential therapy for Helicobacter pylori eradication: a randomised trial. Issue 11 (14th October 2010) - Romano, Marco; Cuomo, Antonio; Gravina, Antonietta G; Miranda, Agnese; Iovene, Maria Rosaria; Tiso, Angelo; Sica, Mariano; Rocco, Alba; Salerno, Raffaele; Marmo, Riccardo; Federico, Alessandro; Nardone, Gerardo
Abstract : Background and aims: Antimicrobial drug resistance is a major cause of the failure of Helicobacter pylori eradication and is largely responsible for the decline in eradication rate. Quadruple therapy has been suggested as a first-line regimen in areas with clarithromycin resistance rate >15%. This randomised trial aimed at evaluating the efficacy of a levofloxacin-containing sequential regimen in the eradication of H pylori -infected patients in a geographical area with >15% prevalence of clarithromycin resistance versus a clarithromycin-containing sequential therapy. Methods: 375 patients who were infected with H pylori and naïve to treatment were randomly assigned to one of the following treatments: (1) 5 days omeprazole 20 mg twice daily + amoxicillin 1 g twice daily followed by 5 days omeprazole 20 mg twice daily + clarithromycin 500 mg twice daily + tinidazole 500 mg twice daily; or (2) omeprazole 20 mg twice daily + amoxicillin 1 g twice daily followed by omeprazole 20 mg twice daily + levofloxacin 250 mg twice daily + tinidazole 500 mg twice daily; or (3) omeprazole 20 mg twice daily + amoxicillin 1 g twice daily followed by omeprazole 20 mg twice daily + levofloxacin 500 mg twice daily + tinidazole 500 mg twice daily. Antimicrobial resistance was assessed by the E-test. Efficacy, adverse events and costs were determined for each group. Results: Eradication rates in the intention-to-treat analyses were 80.8% (95% CI, 72.8% to 87.3%) with clarithromycin sequential therapy, 96.0% (95% CI, 90.9% to 98.7%) with levofloxacin-250 sequential therapy, and 96.8% (95% CI, 92.0% to 99.1%) with levofloxacin-500 sequential therapy. No differences in prevalence of antimicrobial resistance or incidence of adverse events were observed between groups. Levofloxacin-250 therapy was cost-saving compared with clarithromycin sequential therapy. Conclusion: In an area with >15% prevalence of clarithromycin resistant H pylori strains, a levofloxacin-containing sequential therapy is more effective, equally safe and cost-saving compared to a clarithromycin-containing sequential therapy.